2017
DOI: 10.2174/1874210601711010701
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Periodontal Disease and Serum Factors in Patients Undergoing Hemodialysis

Abstract: Background:Chronic renal disease is a common condition with several recognized risk factors. Periodontal disease is a recently suggested risk factor for renal disease. We aimed to assess the relationship between periodontal disease and several serum factors in patients undergoing hemodialysis.Methods:This descriptive cross-sectional study was conducted on 57 patients undergoing hemodialysis. Periodontal examination was done by measuring the mean Pocket Depth (PD), Silness-Löe Plaque Index (PI), Ainamo and Bay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 41 publications
2
17
1
Order By: Relevance
“…As shown in Table 3, to our knowledge, all reports that have investigated changes in serum calcium levels by periodontitis in HD patients showed no significant difference [10,13,36,48]. In contrast, a cross-sectional study reported that higher calcium intake (584.5–1478.5 mg/day) was inversely associated with probing pocket depth (PPD) > 4 mm (adjusted odds ratio; 0.53, 95% CI; 0.30–0.94, p = 0.03) compared to a lower intake group (230.7–393.4 mg/day) [50].…”
Section: Hemodialysismentioning
confidence: 93%
See 3 more Smart Citations
“…As shown in Table 3, to our knowledge, all reports that have investigated changes in serum calcium levels by periodontitis in HD patients showed no significant difference [10,13,36,48]. In contrast, a cross-sectional study reported that higher calcium intake (584.5–1478.5 mg/day) was inversely associated with probing pocket depth (PPD) > 4 mm (adjusted odds ratio; 0.53, 95% CI; 0.30–0.94, p = 0.03) compared to a lower intake group (230.7–393.4 mg/day) [50].…”
Section: Hemodialysismentioning
confidence: 93%
“…Regarding phosphorus in HD patients, the mean/SD serum levels in healthy/gingivitis patients (5.87/1.59 mg/dL) showed a trend towards being higher than in moderate/severe periodontitis (5.29/1.68 mg/dL) patients; however, this difference did not reach statistical significance ( p = 0.084) [10]. In addition, several investigators have shown that serum phosphorus levels in periodontal disease are not significantly different compared to non-gingivitis groups [36,48]. However, in contrast to these results, other investigators showed that serum phosphorus levels in HD patients with periodontitis (mean/SD; 5.02/1.19 mg/dL) were significantly lower ( p = 0.024) than in patients without periodontitis (6.25/1.72 mg/dL) [13].…”
Section: Hemodialysismentioning
confidence: 99%
See 2 more Smart Citations
“…In hemodialysis patients, several negative alterations lead to the progression of MICS [13], which represents the most common cause of death in this population. The patients undergoing hemodialysis are more prone to developing an inflammatory status as well as a state of malnutrition due to multiple factors, which range from the bioincompatibility between blood and dialyzer to the presence of endotoxins in dialysis fluid and access-related infections [14], and emerging non-traditional risk factors [15][16][17][18][19], including exposure to general inflammation [20]. Periodontitis potentially activates inflammatory cells and triggers inflammatory signaling pathways, promoting a low-grade systemic inflammatory status that could compromise clinical outcomes in patients undergoing hemodialysis [21][22][23].…”
Section: Discussionmentioning
confidence: 99%